2020
DOI: 10.1186/s12301-019-0013-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the value of the different variants of abnormal digital rectal examination finding in predicting carcinoma of the prostate: a preliminary report of a two-center study

Abstract: Background: Digital rectal examination is a veritable tool for the clinical diagnosis and screening for carcinoma of the prostate. This study aims to assess the value of the different variables which constitute abnormal digital rectal examination (DRE) findings. Results: Following ethical approval, one hundred and thirty-one men met the inclusion criteria and were enrolled in the study. The peak incidence of abnormal DRE finding was in the 8th decade of life, while the PPV was 66.5%. Of the total, 44 (33.5%) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…PCa diagnosis currently relies on digital rectal examination (DRE) and blood PSA levels followed by a solid biopsy to confirm and characterize the malignancy. DRE sensitivity and specificity are reported to be 80% and 48.6% respectively which makes it dependent on validation via solid biopsy upon palpation and detection of irregularities in the prostate nodules (Irekpita et al, 2020). Although DRE provides significantly higher success rates in detecting high-grade PCa cases when compared to PSA levels, it still shows a limited overall predictive value and high invasiveness (Jones et al, 2018).…”
Section: Current Status Of Diagnostics In Pca and The Need For New Bi...mentioning
confidence: 99%
See 1 more Smart Citation
“…PCa diagnosis currently relies on digital rectal examination (DRE) and blood PSA levels followed by a solid biopsy to confirm and characterize the malignancy. DRE sensitivity and specificity are reported to be 80% and 48.6% respectively which makes it dependent on validation via solid biopsy upon palpation and detection of irregularities in the prostate nodules (Irekpita et al, 2020). Although DRE provides significantly higher success rates in detecting high-grade PCa cases when compared to PSA levels, it still shows a limited overall predictive value and high invasiveness (Jones et al, 2018).…”
Section: Current Status Of Diagnostics In Pca and The Need For New Bi...mentioning
confidence: 99%
“…The following information was collected from the selected articles and tabulated in Tables 2, 3 (Roehrborn and Black, 2011). Authors' name, and publication year (Siegel et al, 2021); type of study design-case-control or cohort (Martin et al, 2018); sample size-number of benign, PCa, and healthy controls (Fenton et al, 2018); the volume of urine used for extraction and method of EV isolation (Irekpita et al, 2020); urine collection time point (pre-or post-DRE or DRE not considered) (Jones et al, 2018); method of miRNAs shortlisting for validation, type of RNA extraction (Balk et al, 2003); normalization of miRNA quantification (Stenman et al, 1999); differentially expressed miRNA reported (Gao et al, 2019); identified miRNA after validation, and (Hugosson et al, 2019) it is predictive value as compared to PSA (Tables 2, 3). Frontiers in Genetics frontiersin.org…”
Section: Data Extractionmentioning
confidence: 99%
“…However, it is a technique with low reproducibility due to the variability between examiners who can interpret the results differently [13,14], since the presence of rectal touch abnormalities can include prostate enlargement, the appearance of suspicious nodules, lobular asymmetry, and hard consistency, among others; the above are not necessarily related to PCa, so they may be related to some other prostate disease. Another disadvantage presented by the DRE test is that the PCa in its early stage may not have the necessary size and rigidity to be palpable [15]. This test additionally causes considerable discomfort, is uncomfortable and embarrassing for patients, and is less accurate than the PSA test [16].…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it has been recommended to perform PSA before DRE (14). Currently, both digital rectal examination and prostate speci c antigen done at the same time are recommended for prostate cancer screening because this technique offers up to 75% diagnostic sensitivity for prostate carcinoma (14,15). PSA testing, digital rectal exam (DRE), and prostate biopsy are the cornerstone of prostate cancer screening (15).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, both digital rectal examination and prostate speci c antigen done at the same time are recommended for prostate cancer screening because this technique offers up to 75% diagnostic sensitivity for prostate carcinoma (14,15). PSA testing, digital rectal exam (DRE), and prostate biopsy are the cornerstone of prostate cancer screening (15). Most clients in our setting come to urology clinic as referrals from primary physicians when DRE has been done.…”
Section: Introductionmentioning
confidence: 99%